2022
DOI: 10.3390/su14148870
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Application of Salicylic Acid and Proline on the Defense Response of Potato Tubers to Newly Emerging Soft Rot Bacteria (Lelliottia amnigena) Infection

Abstract: Potato soft rot, caused by the pathogenic bacterium Lelliottia amnigena (Enterobacter amnigenus), is a serious and widespread disease affecting global potato production. Both salicylic acid (SA) and proline (Pro) play important roles in enhancing potato tuber resistance to soft rot. However, the combined effects of SA and Pro on defense responses of potato tubers to L. amnigena infection remain unknown. Hence, the combined effects of SA and Pro in controlling newly emerging potato soft rot bacteria were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Previous studies indicated that Kh application increased antioxidant activity in pepper plants under saline conditions [ 79 ]. The role of SA treatment in salinity resistance was reported in some previous studies [ 33 , 34 , 35 ]. Increasing GSH and AA contents in plants by SA application could enhance a mechanism to protect plants from the accumulation of ROS under stress conditions [ 80 ].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Previous studies indicated that Kh application increased antioxidant activity in pepper plants under saline conditions [ 79 ]. The role of SA treatment in salinity resistance was reported in some previous studies [ 33 , 34 , 35 ]. Increasing GSH and AA contents in plants by SA application could enhance a mechanism to protect plants from the accumulation of ROS under stress conditions [ 80 ].…”
Section: Discussionmentioning
confidence: 71%
“…Most reports indicate the positive role of foliar application with SA in resistance to salinity in different crops, such as strawberries [ 31 ], cabbage [ 32 ], and cowpea [ 33 ]. Previous studies reported the role of exogenous SA application in mitigating biotic and abiotic stresses [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lelliottia amnigena is included in phylum Pseudomonadota , class Gammaproteobacteria , family Enterobacteriaceae , genus Lelliotia together with L. nimipressuralis (initially known as Erwinia nimipressuralis and then reclassified as Enterobacter nimipressuralis ), and a new species L. jeotgali , which is associated with traditional Korean fermented clam [ 10 ]. Virulence factors are represented by pectinase, protease, pectin lyase, and cellulase [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The assay on potato tuber slices was carried out following the methods reported in the literature ( Mikiciński et al., 2010 ; Osei et al., 2022 ). Briefly, the tubers were first washed under tap water, dried with cleaning paper cloth, dipped for 5 s into 96% ethanol, air dried, and then flamed and cut into 10-mm-thick slices.…”
Section: Methodsmentioning
confidence: 99%